Effects of Downregulation of MicroRNA-181a on H2O2-Induced H9c2 Cell Apoptosis via the Mitochondrial Apoptotic Pathway. (11th February 2014) - Wang, Lei; Huang, He; Fan, Yang; Kong, Bin; Hu, He; Hu, Ke; Guo, Jun; Mei, Yang; Liu, Wan-Li
Abstract : Glutathione peroxidase-1 (GPx1) is a pivotal intracellular antioxidant enzyme that enzymatically reduces hydrogen peroxide to water to limit its harmful effects. This study aims to identify a microRNA (miRNA) that targets GPx1 to maintain redox homeostasis. Dual luciferase assays combined with mutational analysis and immunoblotting were used to validate the bioinformatically predicted miRNAs. We sought to select miRNAs that were responsive to oxidative stress induced by hydrogen peroxide (H2 O2 ) in the H9c2 rat cardiomyocyte cell line. Quantitative real-time PCR (qPCR) demonstrated that the expression of miR-181a in H2 O2 -treated H9c2 cells was markedly upregulated. The downregulation of miR-181a significantly inhibited H2 O2 -induced cellular apoptosis, ROS production, the increase in malondialdehyde (MDA) levels, the disruption of mitochondrial structure, and the activation of key signaling proteins in the mitochondrial apoptotic pathway. Our results suggest that miR-181a plays an important role in regulating the mitochondrial apoptotic pathway in cardiomyocytes challenged with oxidative stress. MiR-181a may represent a potential therapeutic target for the treatment of oxidative stress-associated cardiovascular diseases.